If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3x + -3 = 1.1x + -15 Reorder the terms: -3 + 0.3x = 1.1x + -15 Reorder the terms: -3 + 0.3x = -15 + 1.1x Solving -3 + 0.3x = -15 + 1.1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.1x' to each side of the equation. -3 + 0.3x + -1.1x = -15 + 1.1x + -1.1x Combine like terms: 0.3x + -1.1x = -0.8x -3 + -0.8x = -15 + 1.1x + -1.1x Combine like terms: 1.1x + -1.1x = 0.0 -3 + -0.8x = -15 + 0.0 -3 + -0.8x = -15 Add '3' to each side of the equation. -3 + 3 + -0.8x = -15 + 3 Combine like terms: -3 + 3 = 0 0 + -0.8x = -15 + 3 -0.8x = -15 + 3 Combine like terms: -15 + 3 = -12 -0.8x = -12 Divide each side by '-0.8'. x = 15 Simplifying x = 15
| 5n+9=3n+17 | | 30+2x=4(5x-2) | | 7+3/5(10+35x) | | 1.8(2.57143)+1.5b=3.3 | | 5(2/18)+8d=(-10) | | -1/4=x-2/3 | | n-5/8+n+4/9=19/36 | | 6x+2y=30 | | X^2-10x-128=0 | | -[5z-(15z+1)]=1+(9z+8) | | (y^2)+3y-5=175 | | -2x-4(6.4)=20 | | 5ln(x-1)=10 | | (4x^2+16x-21)/(2x-1) | | 7(x-3)=(x-2) | | -9(3a-4)= | | x-7=-3x-7 | | 4b(6-5b)= | | -5(3n+5)=2 | | x-27=8x+57 | | 11-7x=3-8x | | 7(8+3h)= | | 42/5+42/6 | | y=3+-4x | | x/3+x/2=8/3 | | -x^2+10x+128=0 | | 11x-45=4x+39 | | 2y=24x+2 | | -4(2y-8)-y=-3(y-3) | | 5/6z=5/8 | | x^2-4x+64=0 | | (-a-7b+3)6ab= |